Assessment of biochemical outcomes in patients with primary aldosteronism after adrenalectomy based on CT scan diagnosis of unilateral adenoma without adrenal vein sampling - Zhang, Ming; Bian, Ge; Tian, Jingyan; Yang, Weijie; Wang, Xiaoqing; Chi, Changliang (Frontiers in Oncology, 2022)
Purpose: To assess the surgical outcomes of patients with primary aldosteronism when surgery was based only on CT finding of unilateral adenoma without adrenal vein sampling. Methods: This is a retrospective review of the records of patients who had undergone retroperitoneal laparoscopic adrenalectomy for primary aldosteronism based on CT scan finding of unilateral adenoma and had a follow up of at least 6-12 months from Jan 2012 to Dec 2020 in a single center,decision for adrenalectomy was based on CT scan and adrenal vein sampling (AVS) was not used. The clinical and biochemical outcomes was accessed using the standardized primary aldosteronism surgical outcome(PASO) criteria.Patient’s demographics and preoperative factors were analyzed to assess for independent predictor of surgical success. Results: According to the PASO criteria, 172 patients finally enrolled in the training dataset, and 20 patients enrolled in the validation dataset. In the training dataset, complete clinical success was achieved in 71 patients (41.3%), partial success in 87 (50.6%), and absent success in 14 (8.1%). Biochemical outcomes showed that 151 patients (87.8%) completely cured, 14 patients (8.1%) got a partial biochemical success and an absent biochemical success was found in 7 patients (4.1%). Multivariate logistic regression analysis showed that age, body mass index (BMI), tumor size, mean arterial pressure(MAP), and serum potassium were the most independent factors for incomplete biochemical success. Based on the results of statistical analysis, our study constructed a nomogram prognostic evaluation model for patients after unilateral primary aldosterone surgery. Conclusion: Laparoscopic adrenalectomy for patients with primary aldosteronism base on CT scan finding of a unilateral adenoma without adrenal vein sampling had a high rate of complete biochemical cure at 12 months. Risk factors for incomplete biochemical success include age, BMI, tumor size, MAP, and serum potassium. Our study constructed a nomogram prognostic evaluation model for patients after unilateral primary aldosterone surgery. The nomogram accurately and reliably predicted the incomplete biochemical success. Key words:primary aldosteronism，laparoscopic adrenalectomy，adrenal vein sampling，CT scan，primary aldosteronism surgical outcome